2007
DOI: 10.1167/iovs.06-1034
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Progenitor Cells Derived from Adult Ciliary Body in Mouse, Rat, and Human Eyes

Abstract: Progenitor cells from adult mammalian ciliary body have significant, but limited, proliferation potential and express markers characteristic of other progenitor cells and seen during early retinal development. The ciliary body could be a source of cells for transplantation in experimental rodent eyes and for autotransplantation in human eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 35 publications
0
60
0
6
Order By: Relevance
“…The expression of Oct4 and Pax6 indicated dedifferentiation of the cells from the spheres under the effect of factors of the medium. Presumably, some of them possessed properties of poorly differentiated cells, characterized by expression of Pax6, essential for maintaining the proliferation and differentiation [15,24]. Multipotency of cells from the spheres manifested by their development in the neuronal and epithelial direction.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of Oct4 and Pax6 indicated dedifferentiation of the cells from the spheres under the effect of factors of the medium. Presumably, some of them possessed properties of poorly differentiated cells, characterized by expression of Pax6, essential for maintaining the proliferation and differentiation [15,24]. Multipotency of cells from the spheres manifested by their development in the neuronal and epithelial direction.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the retina may also continue to grow after birth and new cells may be generated during lifespan after injury due to the presence of retinal stem cell (RSCs) resident in a region adjacent to the retina, the ciliary epithelium (CE) located in the pigmented ciliary bodies of the adult mammalian eye (Fig. 3) [11,16,[170][171][172][173]. These multipotent RSCs located in the pigmented ciliary bodies, also designated CE stem cells, express several stem cell markers, including telomerase, neural markers such as nestin, and retinal progenitor markers such as Pax 6 [170][171][172].…”
Section: Ocular Stem Cellsmentioning
confidence: 99%
“…These findings have led to the hypothesis that the adult retina might regenerate during life in other species besides fish and amphibians. Retinal stem cells have also been found in vitro in the ciliary body (CB) [14,15] and the iris [15]. On the one hand, it has been shown that most precursor cells in the ciliary margin may give rise to both epithelial cells and neurons [16,17].…”
Section: Introductionmentioning
confidence: 99%